Comparison between ventriculosubgaleal shunt and extraventricular drainage to treat acute hydrocephalus in adults at Hospital Queen Elizabeth between 2013 and 2015 : a retrospective study - Siaw Nee, Low (2015)
Introduction Hydrocephalus is defined as an inappropriate amount of cerebrospinal fluid (CSF) within the intracranial space at an inappropriate pressure. The decision to treat hydrocephalus is based on its various aetiologies. Transient alterations of CSF hemodynamics due to conditions such as subarachnoid and intraventricular haemorrhages, meningitis, and external compression from tumours may resolve after treatment; thus, temporary CSF diversion can be considered. A ventriculosubgaleal shunt (VSGS) can been used for temporary CSF diversion because it is a simple and rapid method, and establishes CSF decompression without causing electrolyte and nutritional losses. Objectives To study the efficacy of VSGS as a means of temporary CSF diversion, compared to EVD in adult hydrocephalus patients; to evaluate the outcome in terms of avoiding a permanent shunt, and to look for incidences of intracranial complications such as ventriculitis and modified Rankin scale, between the year 2013 and 2015. Methods This is a retrospective review of records. The data has been acquired from case notes of 50 patients with acute hydrocephalus: 26 secondary to intraventricular haemorrhage, ten from aneurysm rupture, eight post-trauma and six from infection. All these patients had undergone cerebrospinal fluid diversion in Hospital Queen Elizabeth II between 2013 and 2015. The patients were followed-up from the date of treatment until the resolution of hydrocephalus, where parameters such as shunt dependency and complications were documented in a pro forma. Results A total of 21 (42%) patients underwent EVD insertion and 29 (58%) underwent VSGS. Thirty-seven (74%) patients did not require a permanent shunt; 24 (64.8%) of them were from the VSGS group (p=0.097). EVD had more intracranial complications (44.1%) compared with VSGS (23.5%), with a statistically significant p value of 0.026. Conclusion While each treatment modality has its own complications, this study shows that VSGS is comparable with EVD as a temporary CSF diversion measure. As there are xvii no statistical differences between these two modalities, VSGS is a viable option that has clinical value, with the possibility of continuation of treatment for such patients in non-neurosurgical centres, as opposed to patients with EVDs. Also, VSGS has statistically significant less intracranial complications compared with EVD.